2012
DOI: 10.1371/journal.pone.0030357
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor FoxO1 Is Essential for Enamel Biomineralization

Abstract: The Transforming growth factor β (Tgf-β) pathway, by signaling via the activation of Smad transcription factors, induces the expression of many diverse downstream target genes thereby regulating a vast array of cellular events essential for proper development and homeostasis. In order for a specific cell type to properly interpret the Tgf-β signal and elicit a specific cellular response, cell-specific transcriptional co-factors often cooperate with the Smads to activate a discrete set of genes in the appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…IIIA). In a previous study, the conditional knockout of FoxO1 in ameloblasts of the teeth was shown to result in a chalky, white tooth phenotype consistent with enamel hypomaturation and attrition 21 . FoxO1-res mice also demonstrated abnormally white, chalky incisors compared with wild-type littermates (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…IIIA). In a previous study, the conditional knockout of FoxO1 in ameloblasts of the teeth was shown to result in a chalky, white tooth phenotype consistent with enamel hypomaturation and attrition 21 . FoxO1-res mice also demonstrated abnormally white, chalky incisors compared with wild-type littermates (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Here, we show that endothelial-specific deletion of FoxO1 essentially phenocopies the full knockout, the only obvious difference being in the formation of the branchial arches. By contrast, embryonic development is not compromised in mice with lineage-specific deletions of FoxO1 in bone 18 , liver 19 , heart 7 , T cells 20 , and teeth enamel 21 . Collectively, these findings suggest that embryonic lethality in the full knockout is attributed primarily to the loss of FoxO1 in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown that ameloblast morphology remains unaltered in Smad3 2/2 mice although the enamel is poorly mineralized due to defective protein removal at the maturation stage (Yokozeki et al, 2003). Recently, it was reported that Smad3 and FoxO1 (transcriptional co-factor for Smads) collaboratively regulate genes involved in enamel formation (Poché et al, 2012). Interestingly, in both Smad3 and FoxO1 mutant teeth, the expression of Ambn, Amelx, Enam, Mmp20 and Klk4 were all significantly downregulated.…”
Section: -Fold) In the Enamel Organs Of Itgb6mentioning
confidence: 96%
“…miR-1271, which was more highly expressed in hDFC, was shown to be one of the miRNAs that target FOXO1. A previous study showed that the FOXO family of transcription factors has an essential role in tooth development and in regulation of the process of biomineralization (23). Based on these results, the miRNAs that are highly expressed in each cell type target and regulate the expression specific mRNAs.…”
Section: Discussionmentioning
confidence: 93%